DNAJB11 predicts a poor prognosis and is associated with immune infiltration in thyroid carcinoma: a bioinformatics analysis. Issue 11 (November 2021) - Sun, Rongxin; Yang, Longyan; Wang, Yan; Zhang, Yuanyuan; Ke, Jing; Zhao, Dong
Objective: To investigate the prognostic value of the co-chaperone protein DnaJ Heat Shock Protein Family (Hsp40) Member B11 (DNAJB11) in thyroid carcinoma (THCA). Methods: This bioinformatics analysis study evaluated the prognostic value of DNAJB11 mRNA levels in THCA based on data from The Cancer Genome Atlas (TCGA). The levels of DNAJB11 mRNA in THCA and normal tissues were compared with Wilcoxon signed rank test. Kaplan–Meier survival curve analysis and Cox regression analysis were performed to evaluate the correlation between DNAJB11 mRNA levels and survival. Gene Ontology (GO) enrichment analysis was used to elucidate the functional enrichment difference. Results: Data from the 502 patients with THCA from the TCGA database were analysed. DNAJB11 mRNA was downregulated in THCA tissues compared with normal tissues. Decreased levels of DNAJB11 mRNA were significantly correlated with T stage, N stage, pathological stage, histological type, extrathyroidal extension and BRAF gene status. The low levels of DNAJB11 mRNA were associated with a shorter progression-free interval. GO enrichment analysis showed that DNAJB11 was involved in immune-related biological processes. Conclusion: Low levels of DNAJB11 mRNA were associated with poor prognosis in THCA.